Entrepreneurship Research inAMJ: What Has Been Published, and What Might the Future Hold? - Ireland, R. Duane; Reutzel, Christopher R.; Webb, Justin W. (Academy of Management Journal, 2005)
This article describes the trends associated with publishing entrepreneurship research in the “Academy of Management Journal” (AMJ), identifies some of the characteristics of the entrepreneurship research that has been published in the past, and offers some expectations about the entrepreneurship research that may be published in the future. The authors state that the amount of entrepreneurship research AMJ is publishing continues to increase. The authors' research indicates that scholars are increasingly interested in studying questions regarding new ventures, international entrepreneurship, and initial public offerings.